2015
DOI: 10.5414/cp202368
|View full text |Cite
|
Sign up to set email alerts
|

Ibuprofen lysinate, quicker and less variable: relative bioavailability compared to ibuprofen base in a pediatric suspension dosage form

Abstract: While S-ibuprofen shows a similar bioavailability for AUC0t, AUC0∞, and Cmax, R-ibuprofen shows suprabioavailability for the lysinate formulation. The rate of absorption of the ibuprofen lysinate suspension is quicker and less variable than that of the ibuprofen base reference suspension and it exhibits a shorter tmax, which is of particular interest for achieving a rapid and homogeneous analgesic and antipyretic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…In order to enhance the dissolution rate of IBU in the stomach, soft gelatin capsules filled with solubilized IBU [14] or IBU salt conjugates, e.g., IBU-arginine [13,15,16] or IBU-lysine [12,17], are used. In particular, it was shown in healthy volunteers that film-coated tablets had 39% lower C max and 3.2 times higher t max (min) values than soft gel capsules of IBU [14].…”
Section: Introductionmentioning
confidence: 99%
“…In order to enhance the dissolution rate of IBU in the stomach, soft gelatin capsules filled with solubilized IBU [14] or IBU salt conjugates, e.g., IBU-arginine [13,15,16] or IBU-lysine [12,17], are used. In particular, it was shown in healthy volunteers that film-coated tablets had 39% lower C max and 3.2 times higher t max (min) values than soft gel capsules of IBU [14].…”
Section: Introductionmentioning
confidence: 99%
“…No severe adverse events were reported. Both curves were well characterized; in all cases AUC 0 t covered more than 80% of the AUC 0 ∞ …”
Section: Resultsmentioning
confidence: 88%
“…Both curves were well characterized; in all cases AUC 0 t covered more than 80% of the AUC 0 ∞. 9 Average concentration-time curves for S-ibuprofen, Ribuprofen, and the sum of both enantiomers of test and reference formulations are shown in Figure 1. The summary of pharmacokinetic parameters obtained with both formulations is presented in Table 1.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Limited data is available on the lysinate formulation of ibuprofen. In 2015 Ferrero-Cafiero et al evaluated the bioavailability of pediatric suspension of lysinate ibuprofen compared to pediatric suspension of standard ibuprofen, in healthy, adult volunteers and found that the rate of absorption of the ibuprofen lysinate suspension is quicker and less variable than that of the ibuprofen base reference suspension and it exhibits a shorter Tmax, which is of particular interest for achieving a rapid and homogeneous analgesic and antipyretic effect 8 . However, to our knowledge, no comparative pharmacokinetic study comparing the early absorption of lysinate ibuprofen and standard ibuprofen in the pediatric population has been carried out so far.…”
Section: F O R P U B L I C a T I O Nmentioning
confidence: 99%